2022
DOI: 10.1111/cen3.12695
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of monoclonal antibodies in neuromyelitis optica: An updated systematic review with meta‐analysis

Abstract: Objective: This is a critical review of studies aiming to assess the safety and efficacy of monoclonal antibodies as compared with the classical regimen in patients with neuromyelitis optica spectrum disorder.Methods: Various electronic databases were searched for original articles reporting results from the use of monoclonal antibodies in neuromyelitis optica spectrum disorder. The Expanded Disability Status Scale and annualized relapse rate score before and after treatment were the primary effect measures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…25 Three systematic reviews 18,20,21 included the same RCT (TANGO trial), which compared TCZ and AZA. 26 Two systematic reviews 20,21 were published in 2021, 1 systematic review 19 was published in 2022 and the fourth systematic review 18 was published in 2023 with the search up to July 21, 2022.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…25 Three systematic reviews 18,20,21 included the same RCT (TANGO trial), which compared TCZ and AZA. 26 Two systematic reviews 20,21 were published in 2021, 1 systematic review 19 was published in 2022 and the fourth systematic review 18 was published in 2023 with the search up to July 21, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…The fourth systematic review 21 did not report the proportion of females. The proportion of patients with AQP4-positive serotype ranged from 14% to 100% across primary studies in 1 systematic review, 19 40% to 100% in the second review, 20 and was reported as 85.8% in patients with TCZ treatment in the third systematic review and 81.3% for the fourth systematic review. 18 One review 20 noted that AZA and mycophenolate mofetil were the most common add-on drugs for TCZ, while the remaining systematic reviews 18,19,21 did not report the add-on drugs.…”
Section: Patient Populationmentioning
confidence: 98%
See 3 more Smart Citations